Printmaking a complete guide to materials & processes - Fick, Bill; Grabowski, Beth (London, UK Laurence King Publishing, 2015)
"Printmaking is a practical and comprehensive guide to printmaking techniques. This fully revised edition includes expanded chapters on digital and hybrid processes, many updated step-by-step process shots, and a brand new 'Print & Make' chapter, which explores the opportunities for creative expression within the many processes available to print makers. The more traditional techniques of screen printing, collgraph, relief, intaglio, lithography and monoprint have also been refereshed with the addition of new images showing a broader range of subject matter, including many contemporary prints and international artists. Each techniqe is explored from the development of the printing or digital matrix, through the different stages of creation to image output, making this an essential volume for beginner and experienced printmakers alike." -- Provided by publisher.
Includes index.
Keywords: Prints -- Technique; Printmaking